User-centred library websites : usability evaluation methods. - George, Carole A., ....- (Oxford : Chandos, 2008)
Targeted at library and information Science (LIS) professionals, this book concentrates on usability evaluation methods used to design usable and user-centred library websites. Aimed at the practitioner, it is a practical guide to methods that are used to gather information from potential users that shape the design of the website based on an iterative design process. From planning the study to writing the report, this book guides the reader through the process of usability evaluation using examples from the author's experience with usability evaluation of library interfaces. It describes usability techniques, procedures, report writing, and design changes that lead to a user-centred interface. Key Features: It is a concise, practical guide to completing usability evaluation methods with an emphasis on creating user-centred library websites. It includes examples that draw on the author's practical experience with usability evaluation. It includes useful guidelines to creating participant
Recruitment letters, scripts, thank you notes, and forms illustrated with practical examples.The Author: Dr George is a Human Factors Researcher with the Carnegie Mellon University Libraries. With an emphasis on improving users' access to information, Ms. George's work focuses on usability studies of library websites and evaluation studies of library services. Her research interests and efforts have been directed towards user-entered interface design and information behaviour studies. Readership: This book is aimed at the professional staff within Library and Information Services, their IT managers, and students in LIS programs. Contents: What is user-centred design? - user-centred design; why design a user-centred website Getting started - preliminary steps; recruiting participants User needs analysis - task analysis; surveys; questionnaires; interviews Designing a website: participatory design - participatory design; affinity programming; card sorting; prototyping Usability inspection methods
- heuristic evaluations; cognitive walkthrough Usability testing the website - planning and preparation; think aloud protocols Communicating the findings - written reports; presentations Appendix - examples Glossary Bibliography Index